2019
DOI: 10.3390/biom9040154
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Delivery of Nanoparticulate Cytochrome C into Glioma Cells Through the Proton-Coupled Folate Transporter

Abstract: In this study, we identified the proton-coupled folate transporter (PCFT) as a route for targeted delivery of drugs to some gliomas. Using the techniques of confocal imaging, quantitative reverse transcription-polymerase chain reaction (qRT-PCR), and small interfering (siRNA) knockdown against the PCFT, we demonstrated that Gl261 and A172 glioma cells, but not U87 and primary cultured astrocytes, express the PCFT, which provides selective internalization of folic acid (FA)-conjugated cytochrome c-containing na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 61 publications
5
14
0
Order By: Relevance
“…Fluorescence studies confirmed that both types of formulations (NP-free and NPcontaining) are internalized by LLC cells, but the NPs are ~3 times more effective inducing cell death. Studies from our lab have shown that this internalization is mediated by the FR [12,15]. In these studies, it was confirmed that cells treated with the optimized Cyt c-PLGA-PEG-FA NPs were undergoing an apoptotic cell death [42].…”
Section: Discussionsupporting
confidence: 56%
See 3 more Smart Citations
“…Fluorescence studies confirmed that both types of formulations (NP-free and NPcontaining) are internalized by LLC cells, but the NPs are ~3 times more effective inducing cell death. Studies from our lab have shown that this internalization is mediated by the FR [12,15]. In these studies, it was confirmed that cells treated with the optimized Cyt c-PLGA-PEG-FA NPs were undergoing an apoptotic cell death [42].…”
Section: Discussionsupporting
confidence: 56%
“…This system offers higher loading capacity in comparison to other nanocarriers because the core of the protein is made 100% of Cyt c, which is the drug itself. Our group has proved in previous studies the selectivity and effectivity of the decorated NPs in vitro, in HeLa cells, and in vivo, in glioma tumors [12,15]. In this study we demonstrate the superiority of the system when compared to an individual, FA-tagged Cyt c system.…”
Section: Introductionsupporting
confidence: 63%
See 2 more Smart Citations
“…A tumor-targeting tissue was faced linking to cyt C AS1411 aptamer, which targets and binds to nucleolin, a nucleolar phosphoprotein which is overexpressed on the surface of HepG2 cells [84]. In another study, cyt C was specifically targeted to glioma cells, exploiting the proton-coupled folate transporter, which is overexpressed in these cells [85]. A folate-receptor targeting amphiphilic copolymer (folic acid-PEG-poly(lactic-co-glycolic acid)) This protein, just like transferrin, is efficiently uptaken by HeLa cells and can be detected in the cytoplasm and in the perinuclear space, suggesting a typical clathrin-coated endocytosis pathway mediated by TfR1.…”
Section: Archaeoglobus Fulgidus-human Chimeric Ferritin For Targeted mentioning
confidence: 99%